Perceptions of self and other: Social judgments and gaze patterns to videos of adolescents with and without autism spectrum disorder. (May 2019) - Grossman, Ruth B; Mertens, Julia; Zane, Emily
Neurotypical adults often form negative first impressions of individuals with autism spectrum disorder and are less interested in engaging with them socially. In contrast, individuals with autism spectrum disorder actively seek out the company of others who share their diagnosis. It is not clear, however, whether individuals with autism spectrum disorder form more positive first impressions of autistic peers when diagnosis is not explicitly shared. We asked adolescents with and without autism spectrum disorder to watch brief video clips of adolescents with and without autism spectrum disorder and answer questions about their impressions of the individuals in the videos. Questions were related to participants' perceptions of the social skills of the individuals in the video, as well as their own willingness to interact with that person. We also measured gaze patterns to the faces, eyes, and mouths of adolescents in the video stimuli. Both participant groups spent less time gazing at videos of autistic adolescents. Regardless of diagnostic group, all participants provided more negative judgments of autistic than neurotypical adolescents in the videos. These data indicate that, without being explicitly informed of a shared diagnosis, adolescents with autism spectrum disorder form negative first impressions of autistic adolescents that are similar to, or lower than, those formed by neurotypical peers.